ANALISIS KESALAHAN KEBAHASAAN DALAM PENULISAN PAPAN REKLAME DAN SPANDUK DI RUANG PUBLIK KAWASAN LAMONGAN: KAJIAN MORFOLOGI - Sholihatun Munawaroh; Ifana Dwi Ratna Suri; Kustina Elisah; Laila Tri Lestari; Mitahul Huda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language plays an important role as a means of communication in public spaces, particularly through billboards and banners that are easily encountered by the public. However, language use in these media still exhibits deviations from the standard rules of Indonesian, especially in terms of morphology. This study aims to identify various types of errors in the use of conventional and non-conventional language on billboards and banners in Lamongan Regency. The research employed a descriptive method with a qualitative approach. Data were collected through literature review, observation, and documentation, and were analyzed using data reduction, data presentation, and conclusion drawing. The findings reveal various morphological errors, including Indonesian–English code mixing, the use of non-standard vocabulary, incorrect adaptation of loanwords, and inappropriate abbreviations. Several erroneous forms identified in the data include stel, peleg, service, photocopy, aja, Rp., telah terlayani, Print, Wi-Fi FREE, Dll, and kost, which do not conform to the standard rules of Indonesian. The appropriate forms are setel, pelek, servis, fotokopi, saja, Rp, terlayani, cetak, internet gratis, dll., and kos. These findings indicate that language use in public media has not yet fully complied with the standards established in the Kamus Besar Bahasa Indonesia (KBBI) and the General Guidelines for Indonesian Spelling (PUEBI). Therefore, greater awareness among the public, business owners, and public media producers regarding morphological principles and Indonesian language standards is needed to promote more effective, efficient, communicative, and linguistically appropriate language use in public spaces.